Network Security: Spoofing-The Online Attacks (International Journal of Engineering and Computer Science, 2014)
The main objective of this paper is to aware the computer users or other novice users about spoofing attacks. Spoofing means pretending something you are not, it is done in order to gain unauthorized access It is mainly the kind of attack that may harm the users in one or many ways depending upon the type of attack, during the spoofed attack attacker not only see our private information like password, user name, account number we type but also modify that precious information. There may be various types of spoofing attacks like web spoofing, URL spoofing ,e-mail spoofing ,IP spoofing etc here we describe the various type of spoofing attack &some useful method for prevent those internet attacks.